2005
DOI: 10.1051/rnd:2005010
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian effects of a high lactose diet in the female rat

Abstract: -Young women with galactosemia experience ovarian failure at a very early age raising concern about the ovarian toxicity of galactose. While galactose may be present in the diet as a monosaccharide, it is predominantly derived from cleavage of the disaccharide lactose within the intestine. Our previous studies in animals have shown that high galactose diets inhibit ovarian follicular development and long-term exposure to high lactose diets retards growth of rats. The objective of the present study was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 20 publications
3
31
0
1
Order By: Relevance
“…An animal study found significantly lower concentrations of estradiol and elevated FSH and LH concentrations in rats fed high amounts of galactose, a breakdown component of lactose, compared with controls (14). In addition, progesterone concentrations were significantly decreased in rats after lactose treatment, whereas no differences were found in serum concentrations of estradiol (13). Here, we did not detect any associations between dairy food intake and lactose and progesterone, but our overall results imply modest changes in reproductive hormones, particularly estradiol and LH, with higher consumption of these foods.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An animal study found significantly lower concentrations of estradiol and elevated FSH and LH concentrations in rats fed high amounts of galactose, a breakdown component of lactose, compared with controls (14). In addition, progesterone concentrations were significantly decreased in rats after lactose treatment, whereas no differences were found in serum concentrations of estradiol (13). Here, we did not detect any associations between dairy food intake and lactose and progesterone, but our overall results imply modest changes in reproductive hormones, particularly estradiol and LH, with higher consumption of these foods.…”
Section: Discussionmentioning
confidence: 98%
“…The biological mechanisms that support an association between dairy food intake and ovulatory function are largely unknown. However, impaired ovarian function was observed in rats fed excessive amounts of lactose (13) and galactose (14), which points to potential biological pathways. These results highlight the need for further study of dairy food intake and reproductive function, particularly among healthy women.…”
Section: Introductionmentioning
confidence: 99%
“…PDE4 is a member of the PDE superfamily that has been identified in ovarian granulosa cells and purposed to play a role in regulation of gonadotropin action [32]. However, cAMP-PDE activity in ovarian follicles is mainly related to PDE3, which is present in oocytes [29,[33][34][35]. Together, they may lead to an increase in PDE activity in ovaries treated with eCG, but the increase is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Serial sections were mounted on 3 slides, deparaffinized with xylene, hydrated with successive decreasing concentrations of ethanolin water, and then stained with hematoxylin and eosin (HE). The section with the largest area was chosen for analysis to count the numbers of preantral, antral and atretic follicles, and corporalutea [24]. Atretic follicles were confirmed when one of the following characteristics was observed, such as the presence of pyknosis in the granulose cell, granulosa cells present in the follicular fluid, or theca cell hypertrophy.…”
Section: Methodsmentioning
confidence: 99%